2015
DOI: 10.1038/srep16347
|View full text |Cite
|
Sign up to set email alerts
|

Gamma oscillations in V1 are correlated with GABAA receptor density: A multi-modal MEG and Flumazenil-PET study

Abstract: High-frequency oscillations in the gamma-band reflect rhythmic synchronization of spike timing in active neural networks. The modulation of gamma oscillations is a widely established mechanism in a variety of neurobiological processes, yet its neurochemical basis is not fully understood. Modeling, in-vitro and in-vivo animal studies suggest that gamma oscillation properties depend on GABAergic inhibition. In humans, search for evidence linking total GABA concentration to gamma oscillations has led to promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
57
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 60 publications
12
57
1
Order By: Relevance
“…The latter measure has been proposed as an index of local GABA concentration [Muthukumaraswamy et al, 2009] and GABA A receptor density [Kujala et al, 2015], two factors that could potentially influence the variability of our peak frequency reliability estimates. We used Pearson's r coefficient to correlate peak gamma frequency, in each experimental session, with peak frequency reliability, as measured by the percentage of bootstrap iterations within ±1.2 Hz of the bootstrap distribution mode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter measure has been proposed as an index of local GABA concentration [Muthukumaraswamy et al, 2009] and GABA A receptor density [Kujala et al, 2015], two factors that could potentially influence the variability of our peak frequency reliability estimates. We used Pearson's r coefficient to correlate peak gamma frequency, in each experimental session, with peak frequency reliability, as measured by the percentage of bootstrap iterations within ±1.2 Hz of the bootstrap distribution mode.…”
Section: Resultsmentioning
confidence: 99%
“…Cousijn et al, 2014; Muthukumaraswamy et al, 2009]. Invigorating this debate, a very recent flumazenil‐positron emission tomography (PET) study demonstrated a positive correlation between the frequency of visually induced gamma oscillations and the density of GABA A receptors in early visual areas [Kujala et al, 2015]. Further contribution to the translation of animal models to humans has come from studies combining MEG, to record cortical activity, with the use of pharmacological agents, to modulate neurotransmission [Hall et al, 2010; Muthukumaraswamy, 2014].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still difficult to fully interpret many of the obtained measures due to the complexity of the underlying neural sources. In this respect, multimodal approaches combining MEG (or EEG) with imaging of the dopamine or GABA neurotransmitter systems (using PET) may help improve our interpretation of the observed changes in oscillatory dynamics (Muthukumaraswamy et al, 2013;Kujala et al, 2015). While we found in our studies that DBS and medication affected cortical gamma oscillations, their functional and behavioral implications are not easily discernable.…”
Section: Perspectivescontrasting
confidence: 39%
“…While we found in our studies that DBS and medication affected cortical gamma oscillations, their functional and behavioral implications are not easily discernable. Hence, combining MEG experimentation similar to the one adopted in this thesis with behavioral measures as well as imaging techniques mapping out relevant details on relevant neuroreceptors, such as GABA receptor density (Kujala et al, 2015), may improve the neurophysiological basis for interpreting our current results, and thus our understanding of the impact of treatments on particular neuronal elements, and their relation to behavioral effects and the possible underlying mechanisms.…”
Section: Perspectivesmentioning
confidence: 99%